Family care-giving and religion: Evidence from micro-data in the United States - Yoshihiko Kadoya; David Green (Osaka University, Institute of Social and Economic Research (ISER), 2013)
Purpose: Examining the linkage between self-reported ethnicity and the propensity for family-based informal health care, this study considers cultural connections to religion as a possible explanation for ethnic difference. Design and Methods: Nation-wide survey respondents (N = 2,126) were selected on the basis of having a parent requiring long-term care now or in the near future, and weighted according to age, gender, and self-reported Hispanic ethnicity. A probit analysis tested the association of Hispanic ethnicity, as well as several other explanatory variables, with the possibility of the respondent assuming the primary caregiving role for the elderly family member. Results: While there was a significant association between Hispanic ethnicity and family elder care, there was no significant relationship between religion and family elder care. There was additionally no significant association with level of income. Implications: This research reiterates, using recent micro-data, that there is indeed a connection between ethnicity and family elder care. However, we show that religion is not one of the facets underlying such ethnic difference. While we have taken an initial step in quantitatively defining cultural attributes, more research is needed to determine where ethnic differences may originate.
Keywords: I30; Z1; 330; family care-giving; religion; ethnicity; household survey; population aging